Organocatalytic Combinatorial Synthesis of Quinazoline, Quinoxaline and Bis(indolyl)methanes - Malamiri, Fatemeh; Khaksar, Samad; Badri, Rashid; Tahanpesar, Elham (Combinatorial Chemistry & High Throughput Screening, 2020)
Aims and Objective: An efficient and practical procedure for the synthesis of heterocyclic compounds such as quinazolines, quinoxalines and bis(indolyl)methanes was developed using 3,5-bis(trifluoromethyl) phenyl ammonium hexafluorophosphate (BFPHP) as a novel organocatalyst. Materials and Methods: All of the obtained products are known compounds and identified by IR, 1HNMR, 13CNMR and melting points. Result: Various products were obtained in good to excellent yields under reaction conditions. Conclusion: The BFPHP organocatalyst demonstrates a novel class of non-asymmetric organocatalysts, which has gained much attention in green chemistry.
Keywords: Organocatalyst